2011
DOI: 10.1007/s10555-011-9325-9
|View full text |Cite
|
Sign up to set email alerts
|

Potential roles for prions and protein-only inheritance in cancer

Abstract: Inherited mutations are known to cause familial cancers. However, the cause of sporadic cancers, which likely represent the majority of cancers, is yet to be elucidated. Sporadic cancers contain somatic mutations (including oncogenic mutations), however, the origin of these mutations is unclear. An intriguing possibility is that a stable alteration occurs in somatic cells prior to oncogenic mutations and promotes the subsequent accumulation of oncogenic mutations. This review explores the possible role of prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 154 publications
(238 reference statements)
1
33
0
3
Order By: Relevance
“…Extensive analysis of TRAMP mice has also revealed that they harbor AR single base substitution within their tumors, and the incidence of AR mutation increases with castration[54]. As one of the first models, TRAMP has been utilized to validate genes involved in PCa progression[55], as well as chemopreventative approaches and novel therapeutics[56]. …”
Section: Mouse Models Of Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive analysis of TRAMP mice has also revealed that they harbor AR single base substitution within their tumors, and the incidence of AR mutation increases with castration[54]. As one of the first models, TRAMP has been utilized to validate genes involved in PCa progression[55], as well as chemopreventative approaches and novel therapeutics[56]. …”
Section: Mouse Models Of Prostate Cancermentioning
confidence: 99%
“…We would like to thank all researchers whose work we have cited, those whose contributions were omitted in the interest of space constraints, and those whose omission was unintentional. The brevity of this review is greatly attributable to the excellent and exhaustive reviews on mouse models[55,138-140], mouse PCa pathology[9,10], and human PCa progression[139] published previously.…”
mentioning
confidence: 99%
“…Wildtype p53 aggregates were shown to enter HeLa and NIH3T3 cells (most likely via macropinocytosis) and induce intracellular p53 aggregation. 13 In their review article, Antony et al 68 emphasized the likely role of protein-only inheritance and prions in cancer. Genetic studies with yeast showing that prions confer dominant phenotypes with cytoplasmic inheritance to these organisms indicate that several of these proteins have mammalian functional homologs.…”
Section: In Silico Analyses Of Aggregation-prone Sequences Of P53 P6mentioning
confidence: 99%
“…Nevertheless, MCL algorithm results point toward a possible relationship between Clusterin and Aker or APrp, a finding that remains to be elucidated. Additional proteins of this cluster are associated with transcriptional regulation and pre-mRNA splicing, since the over-expression of prions influences normal cellular proteins, participating in apoptosis or cell signaling [104]. Transthyretin, a potent inhibitor of Aβ [72], created a separate cluster together with Small ubiquitin-related modifier 3.…”
Section: Resultsmentioning
confidence: 99%